Bauran Pemasaran Rijan Mineral Water dan Pengarunya terhadap Keputusan Pembelian Konsumen di Mojokerto - Slamet Wahyudi (FADZAT: Jurnal Ekonomi Syariah, 2021)
The purposes of this study are: 1) Analyzing the product has a significant effect on purchasing decisions. 2) Analyzing the price has a significant effect on purchasing decisions. 3) Analyzing the place has a significant effect on purchasing decisions. 4) Analyzing promotion has a significant effect on purchasing decisions. 5) Analyzing product, price, place and promotion have a joint effect on purchasing decisions. 6) To find out which products, prices, places and promotions have the greatest influence on purchasing decisions. Based on considerations of time, effort, and funds, as well as the scope of the problem and the large number of subjects when the research was carried out in August 2020. The population in this study was Rijan Mineral Water Consumers in Mojokerto, the population in this study was 96 people. The sampling method is a census or saturated sample where all members of the population are sampled, while data analysis uses multiple linear regression. From the results of the study, it can be concluded as follows: 1) The product has a significant effect on purchasing decisions. 2) Price has no significant effect on purchasing decisions. 3) Compensation has no significant effect on performance. 4) Promotion has a significant effect on purchasing decisions. 5) Product, price, place and promotion have a joint effect on purchasing decisions.